Single-mode lasing based on PT-breaking of two-dimensional photonic higher-order topological insulator - Zhu, Bofeng (2021)
Topological lasers are a new class of lasers that seek to exploit the special properties of topological states of light. A typical limiting factor in their performance is the existence of non-topological states with quality factors comparable to the desired topological states. We show theoretically that by distributing uniform gain and loss on two sublattices of a two-dimensional higher-order topological insulator (HOTI) lattice, single-mode lasing based on topological corner states can be sustained over a wide range of pump strengths. This behavior stems from the parity/time-reversal breaking of the topological corner states, which supplies them with more effective gain than the edge and bulk states, rather than through localized pumping of the domain corners. These results point to opportunities for exploiting non-Hermitian phenomena and designing compact high performance topological lasers.